Students' perceptions towards the influences of social media on students' academic engagement at a tertiary institution: a case study on the use of Facebook and Twitter at Rhodes University - Moongela, Harry (Rhodes University, Faculty of Commerce, Department of Information Systems, 2018)
The use of social media has become an integral part of student's academic lives and has had an impact on students' academic engagement in tertiary institutions. Subsequently, researchers have shown an interest in investigating the impact of social media on students' academic engagement. Despite the fact that researcher have shown interest, there still remains a limited number of studies that have discussed the effects of social media on students' academic engagement, particularly within a South African context. Also, studies that have been carried have revealed limited and mixed findings. This study then aims to further investigate whether the exposure of students to social media has an effect on their academic engagement and how tertiary institutions together with students can use social media to improve students' academic engagement. A qualitative research method using an interpretive (inductive) approach is carried out to find out students' perceptions towards the use of social media and its influence on students' academic engagement. The study then reveals recommendations from students' perceptions on the effective ways of using social media to benefit students' academic engagement in tertiary institutions.
Keywords: Facebook (Firm); Twitter (Firm); Social media in education -- South Africa -- Makhanda; Motivation in education -- South Africa -- Makhanda; Education, Higher -- Effect of technological innovations on -- South Africa -- Makhanda; Rhodes University